On the Seasonal Signal of the Filchner Overflow, Weddell Sea, Antarctica - Darelius, Elin Maria K; Strand, Kjersti Opstad; Østerhus, Svein; Gammelsrød, Tor; Årthun, Marius; Fer, Ilker (Journal of Physical Oceanography, 2014)
Keywords: Sørishavet; Weddellhavet; bunnvann; isshelf; kontinentalsokkel; kontinentalsokler; oseanografi; sjøvann

Low melt rates with seasonal variability at the base of Fimbul Ice Shelf, East Antarctica, revealed by in situ interferometric radar measurements - Langley, Kirsty; Kohler, Jack; Sinisalo, Anna; Øyan, Mats Jørgen; Hamran, Svein Erik; Hattermann, Tore; Matsuoka, Kenichi; Nøst, Ole Anders; Isaksson, Elisabeth (Geophysical Research Letters, 2014)
Basal melt is a major cause of ice shelf thinning affecting the stability of the ice shelf and reducing its buttressing effect on the inland ice. The Fimbul ice shelf (FIS) in Dronning Maud Land (DML), East Antarctica, is fed by the fast-flowing Jutulstraumen glacier, responsible for 10% of ice discharge from the DML sector of the ice sheet. Current estimates of the basal melt rates of the FIS come from regional ocean models, autosub measurements, and satellite observations, which vary considerably. This discrepancy hampers evaluation of the stability of the Jutulstraumen catchment. Here, we present estimates of basal melt rates of the FIS using ground-based interferometric radar. We find a low average basal melt rate on the order of 1 m/yr, with the highest rates located at the ice shelf front, which extends beyond the continental shelf break. Furthermore, our results provide evidence for a significant seasonal variability.
Keywords: Dronning Maud Land; geofysikk; glasiologi; innlandsis; isbre; isshelf; kontinentalsokkel; smelting

Distribution of total alkalinity and pH in the Ross Sea (Antarctica) waters during austral summer 2008 - Rivaro, Paola; Messa, Roberta; Ianni, Carmela; Magi, Emanuele; Budillon, Giorgio (Polar Research, 2014)
Measurements of total alkalinity (AT) and pH were made in the Ross Sea in January–February 2008 in order to characterize the carbonate system in the Ross Sea and to evaluate the variability associated with different water masses. The main water masses of the Ross Sea, Antarctic Surface Water, High Salinity Shelf Water (HSSW), Deep Ice Shelf Water, Circumpolar Deep Water (CDW) and Antarctic Bottom Water, were identified on the basis of the physical and chemical data. In particular, the AT ranged between 2275 and 2374 µmol kg−1 with the lowest values in the surface waters (2275–2346 µmol kg−1), where the influence of the sea-ice melting and of the variability of the physical properties was significant. In the deep layers of the water column, the AT maxima were measured in correspondence to the preferential pathways of the spreading HSSW. The pH had variable values in the surface layer (7.890–8.033) with the highest values in Terra Nova Bay and Ross Sea polynyas. A low pH (7.969±0.025) traced the intrusion of the CDW in the Ross Sea shelf area. All samples revealed waters that were oversaturated with respect to both calcite and aragonite, but near corrosive levels of aragonite saturation state (Ω ca. 1.1–1.2) were associated with the entrainment of CDW over the slope. Aragonite undersaturation is of particular concern for the zooplankton species comprising to calcifying organisms such as pteropods. The partial pressure of CO2 at the sea surface was undersaturated with respect to the atmospheric value, particularly in Terra Nova Bay and the Ross Sea polynyas, but a large variability in the sea–air CO2 fluxes was observed associated with different responses in the strength of the biological and physical processes. Keywords: Total alkalinity; pH; saturation state; Terra Nova Bay polynya; Ross Sea.
Keywords: Rosshavet; Sørishavet; havis; hydrografi; hydrokjemi; kjemiske analyser; klimaendringer; kontinentalsokkel; sjøis; vannmasser; zooplankton